2014
DOI: 10.1080/02640414.2014.951953
|View full text |Cite
|
Sign up to set email alerts
|

How do they make it look so easy? The expert orienteer’s cognitive advantage

Abstract: Expertise in sport can appear so extraordinary that it is difficult to imagine how "normal" individuals may achieve it. However, in this review, we show that experts in the sport of orienteering, which requires on-foot navigation using map and compass through wild terrain, can make the difficult look easy because they have developed a cognitive advantage. Specifically, they have acquired knowledge of cognitive and behavioural strategies that allow them to circumvent natural limitations on attention. Cognitive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 23 publications
4
18
0
2
Order By: Relevance
“…Manuscript to be reviewed are consistent with those obtained from interviews (Eccles & Arsal, 2015). This research found that expert orienteers have a strong ability to simplify maps and focus only on the information related to the task.…”
Section: Introductionsupporting
confidence: 61%
“…Manuscript to be reviewed are consistent with those obtained from interviews (Eccles & Arsal, 2015). This research found that expert orienteers have a strong ability to simplify maps and focus only on the information related to the task.…”
Section: Introductionsupporting
confidence: 61%
“…With the development of eye movement technology, the visual search strategy of orienteers can be measured more precisely as compared with the research methods of interview and self-report. Zhu et al (2011) conducted eye-tracking research on competent players and novices, the results of which are consistent with those obtained from interviews (Eccles & Arsal, 2015). This research found that expert orienteers have a strong ability to simplify maps and focus only on the information related to the task.…”
Section: Introductionsupporting
confidence: 52%
“…The second day we observed faster performance times, lower intensity of dysfunctional psychobiosocial states, and improved visual attention and attention/mental flexibility ( Table 2 and Fig 2 ). These results highlight the impact of the cognitive burden usually associated with orienteering race that is added to the physical load [ 15 ]. Findings are also aligned with our last study hypothesis (H 3 ) stating that a substantial reduction in the cognitive load of the race, due to the familiarity with the course, would result in enhanced psychophysical states and improved performance.…”
Section: Discussionmentioning
confidence: 99%
“…This implies that they plan a route from the map during the race. Successful performance requires considerable visual attention to critical cues from the map, the environment, and the travel [ 15 ]. Attending simultaneously to the three sources of information and making effective decisions under time constraints and competitive stress entails complex and dynamic processes of perception, encoding, retrieval, decision making, and emotion regulation.…”
Section: Introductionmentioning
confidence: 99%